Fenomena Penundaan Perkawinan oleh Wanita Karir ditinjau dari Hukum Islam (Studi di Kecamatan Medan Kota) - Putri Zaronah; Milhan Milhan (UIN Fatmawati Sukarno Bengkulu, 2025)
Abstract: This study examines the practice of marriage postponement among career women in Medan Kota District and analyzes it from an Islamic legal perspective. The issues discussed are the factors driving marriage postponement and how these reasons are positioned within Islamic legal considerations. This study uses a qualitative approach with an empirical normative design. Data were obtained through interviews, observations, and document reviews, then analyzed descriptively and interpretively to connect field findings with relevant Islamic legal concepts. The results indicate that marriage postponement is generally influenced by an orientation toward economic stability, self-development, educational attainment, and work demands and family expectations. Under Islamic law, marriage postponement is not automatically prohibited, but it becomes problematic when it triggers a violation of religious ethical boundaries or opens up the risk of greater harm. Therefore, marriage postponement can be viewed as a permissible choice if it is based on rational considerations, accompanied by the ability to protect oneself, and directed toward achieving benefits and preventing harm.Keywords: marriage postponement, career women, Islamic law, Medan Kota, empirical normative. Abstrak: Penelitian ini mengkaji praktik penundaan perkawinan pada wanita karier di Kecamatan Medan Kota serta menganalisisnya dalam perspektif hukum Islam. Masalah yang dibahas adalah faktor-faktor yang mendorong penundaan perkawinan dan bagaimana alasan tersebut diposisikan dalam pertimbangan hukum Islam. Penelitian ini menggunakan pendekatan kualitatif dengan desain normatif empiris. Data diperoleh melalui wawancara, observasi, dan telaah dokumen, lalu dianalisis secara deskriptif interpretatif untuk menghubungkan temuan lapangan dengan konsep-konsep hukum Islam yang relevan. Hasil penelitian menunjukkan bahwa penundaan perkawinan umumnya dipengaruhi oleh orientasi pada stabilitas ekonomi, pengembangan diri, pencapaian pendidikan, dan tuntutan kerja serta ekspektasi keluarga. Dalam hukum Islam, penundaan perkawinan tidak otomatis terlarang, namun menjadi bermasalah ketika memicu pelanggaran batas etika agama atau membuka risiko kerusakan yang lebih besar. Karena itu, penundaan perkawinan dapat dipandang sebagai pilihan yang dibolehkan apabila didasarkan pada pertimbangan yang rasional, disertai kemampuan menjaga diri, dan diarahkan pada tercapainya kemaslahatan serta pencegahan kemudaratan.Kata Kunci: penundaan perkawinan, wanita karier, hukum Islam, Medan Kota, normatif empiris.